Application of STBM Pillars in the Household on Stunting Incidents - Normila Normila; Resna Maulia (Sarana Ilmu Indonesia (salnesia), 2022)
Children who grow up in an environment with poor sanitation will be at greater risk of disease and will likely continue to have a higher recurrence. This is what causes their growth to be stunted and stunted. This study aimed to analyze the relationship between the implementation of the 5 STBM pillars and the incidence of stunting in the Bukit Rawi Health Center work area, Pulang Pisau Regency. The research method was an analytic observational with a case-control design, namely by comparing a group of toddlers who suffered from stunting with another group who did not suffer from stunting to assess the relationship between causal variables. This research was conducted in the working area of the Bukit Rawi Public Health Center, Pulang Pisau Regency. The minimum sample size was 23 toddlers for the case group and 23 for the control group, so the minimum total sample in this study was 46. Univariate analysis in the frequency distribution of the dependent and independent variables tabulated in the tabular form includes data on characteristics, the incidence of stunting, and the implementation of STBM pillars. The results of the study showed that the application of the pillar STBM (Community-Based Total Sanitation), which had a relationship with the incidence of stunting in the working area of the Bukit Rawi Public Health Center in Pulang Pisau Regency, was the application of Pillar 2, namely the habit of CTPS, Pillar 3 PAMRT and Pillar 4 PSRT with a p-value <0,05.